2020
DOI: 10.1002/cncy.22399
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of p16 expression in FNA specimens from head and neck squamous cell carcinoma and correlation with HPV status

Abstract: Background This study investigated p16 by immunohistochemistry (IHC) on cellblocks (CBs) and human papillomavirus (HPV) by polymerase chain reaction (PCR) in fine‐needle aspiration (FNA) of head and neck squamous cell carcinoma (HNSCC). Methods Receiver operating characteristic (ROC) curve analysis was used to assess test performance in CBs compared with p16 IHC in 42 surgical specimens from patients with HNSCC and in correlation with HPV by PCR in cytology specimens. The study assessed HPV by PCR in FNA speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Immunohistochemical approaches, including direct detection of HPV-encoded proteins or alterations in p16 expression, have been investigated, but more recent studies suggest that these methods are prone to false-positive results [13,22,41,46,49,51,53,55,56,58,59,82]. In particular, it has been found that many lesions negative for HPV express p16 [49,58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical approaches, including direct detection of HPV-encoded proteins or alterations in p16 expression, have been investigated, but more recent studies suggest that these methods are prone to false-positive results [13,22,41,46,49,51,53,55,56,58,59,82]. In particular, it has been found that many lesions negative for HPV express p16 [49,58].…”
Section: Discussionmentioning
confidence: 99%
“…Considerable variability in the correlation of HPV infection with squamous lesions has been reported, and this may be due to the variety of methods for both sampling and viral detection [31,35,46,47]. Immunohistochemical approaches, including direct detection of HPV-encoded proteins or alterations in p16 expression, have been investigated, but more recent studies suggest that these methods are prone to false-positive results in conjunctival lesions [13,22,34,41,46,[48][49][50][51][52][53][54][55][56][57][58][59]. Historically, HPV DNA was detected with Southern blotting or in-situ hybridization assays, which can have poor sensitivity, and polymerase chain reactions (PCR), with high false-positive rates [31,47].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the interpretation of p16 IHC in FNA cell blocks is challenging because of staining variation and controversial cutoffs for a positive result. 12,[15][16][17][18][19] The use of RNAScope can confirm p16 IHC results, but it does not provide the HPV-16 status, which is a requirement for clinical trials at our institution. For these reasons, we previously validated and used 2 commercial HPV testing assays, the Cervista HPV-16/18 and HPV HR assays (Hologic, Inc, Bedford, Massachusetts), for determining the HPV status in head and neck FNA specimens.…”
Section: Cancer Cytopathology July 2022mentioning
confidence: 99%
“…First, cell block material is not always available, but when it is, low cellularity and extensive necrosis often preclude p16 IHC. Second, the interpretation of p16 IHC in FNA cell blocks is challenging because of staining variation and controversial cutoffs for a positive result 12,15‐19 . The use of RNAScope can confirm p16 IHC results, but it does not provide the HPV‐16 status, which is a requirement for clinical trials at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…While a positive p16 IHC result in surgical pathology specimens is defined as “greater than or equal to 70% nuclear and cytoplasmic staining of at least moderate intensity”, 71 the criteria for detecting HPV using p16 in cytological material are not well defined, and the threshold for a positive p16 result needs to be individually validated in each laboratory 72–75 . A cut‐off of greater than or equal to 40% expression in tumour cell clusters may be appropriate for p16 positivity in CB specimens 76 . Negative HPV testing results in cytological material should be repeated if a subsequent surgical pathology specimen becomes available 71 .…”
Section: Immunocytochemistry For Human Papillomavirus (Hpv)‐related Squamous Cell Carcinomas Of the Head And Neckmentioning
confidence: 99%